Local Allergic Rhinitis: Diagnosis and management protocol - Santos, Cláudia (2023)
Aim: Propose a protocol for diagnosis and management of Local Allergic Rhinitis. Material and Methods: Literature review of articles published in english on PubMed database, between 2000 and 2021. Results: Clinically Local Allergic Rhinitis manifestations are similar to allergic rhinitis, however prick tests and specific-IgE serum levels are negative. The diagnosis requires a positive response during a Nasal Allergen Provocation Test. The therapeutic algorithm consists of allergen avoidance measures and pharmacotherapy. When these measures are insufficient to control symptoms, specific immunotherapy can be administered to Local Allergic Rhinitis patients. Conclusions: Local Allergic Rhinitis is a new rhinitis phenotype and is underdiagnosed, affecting a significant proportion of patients diagnosed with non-allergic rhinitis. The implementation of Nasal Allergen Provocation Test in rhinitis diagnostic algorithms is essential for early recognition of Local Allergic Rhinitis and management of the correct therapeutic approach.